2022
DOI: 10.3389/fmars.2022.987872
|View full text |Cite
|
Sign up to set email alerts
|

Use of valvometry as an alert tool to signal the presence of toxic algae Alexandrium catenella by Mytilus edulis

Abstract: Valvometry is a non-invasive technique used to continuously monitor gaping behaviour of bivalves at high frequency. In previous laboratory studies, valvometry has revealed a behavioural sensitivity of bivalves to the presence of toxic microalgae in seawater. However, the application of valvometry as an early-warning system for detecting natural occurrences of toxic microalgae and their resulting toxicity in bivalves remains largely unexplored. In this study, valvometry was used to characterise changes in blue … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 60 publications
1
6
0
Order By: Relevance
“…After this initial 24 h period, A. catenella was introduced at a concentration of 10,000 cells L −1 for 42 h (T1 period). This A. catenella concentration aligns with the maximum concentration used by Durier et al ( 2022) [14] and ensured the regulatory limit for bivalve harvest. Following the T1 period, the water in each of the tanks was completely replaced, and mussels were exposed to Tetraselmis suecica, a non-toxic alga, at a concentration of 5000 cell mL −1 for the next 24 h (T2 period).…”
Section: Experimental Designsupporting
confidence: 85%
See 4 more Smart Citations
“…After this initial 24 h period, A. catenella was introduced at a concentration of 10,000 cells L −1 for 42 h (T1 period). This A. catenella concentration aligns with the maximum concentration used by Durier et al ( 2022) [14] and ensured the regulatory limit for bivalve harvest. Following the T1 period, the water in each of the tanks was completely replaced, and mussels were exposed to Tetraselmis suecica, a non-toxic alga, at a concentration of 5000 cell mL −1 for the next 24 h (T2 period).…”
Section: Experimental Designsupporting
confidence: 85%
“…When mussels were exposed to A. catenella in the current study, the most notable response was an avoidance behaviour with a recorded rise in the number of valve closures and a prolonged valve closure duration. It is noteworthy that Durier et al (2022) [14] reported a contrasting behavioural response, since mussels in that study displayed a decrease in valve closures in the presence of toxic dinoflagellates. The contrasting behavioural responses between the two studies could perhaps be due to different concentrations of A. catenella which was higher in the present study than in Durier et al (2022) [14].…”
Section: Discussionmentioning
confidence: 61%
See 3 more Smart Citations